Heterogeneous catalytic oxidation regeneration of desulfurization-rich liquor with Fe3+ modified chitosan - Liu, Zhihao; Chen, Zhijie; Chen, Qian; Liu, Luwei; Wang, Yingjie; Shu, Peng; Zhong, Yu; Sun, Zeqin; Qiu, Kui (Frontiers in Environmental Engineering, 2023)
To solve the problem of pipeline blockage caused by sulfur deposition in industrial gas wet oxidative desulfurization operations, this study developed an iron-modified chitosan catalyst for the catalytic oxidation regeneration of conventional wet oxidative desulfurization-rich liquids. Detailed characterization results show that Fe3+ species are successfully coordinated with the chitosan substrate. The results of desulfurization and regeneration experiments showed that the Fe3+-modified chitosan could effectively regenerate the desulfurization waste stream and remain stable in the acidic desulfurization stream. The powdered iron-based modified chitosan catalyst prepared with a mass ratio of chitosan to FeCl3 of 1:5 and glutaraldehyde of 12.5% by mass has better catalytic performance than the microbead counterpart. The regeneration performance of the catalyst was evaluated by the desulfurization performance of the regenerated desulfurization solution. The iron-based modified chitosan shows a good regeneration performance, and the loss of Fe content is less than 1.5% after five runnings. This study provides an efficient way to develop cost-effective catalysts for the regeneration of wet oxidative desulfurization-rich liquids.